The Effect of Diabetes Camp on Glycemic Variability in Children and Adolescents with Type 1 Diabetes Mellitus - Aysun Ata; Gürel Arı; Hafize Işıklar; Günay Demir; Yasemin Atik Altınok; Betül Ersoy; Samim Özen; Şükran Darcan; Damla Gökşen (Galenos Yayinevi, 2021)
Aim:Glycemic variability can be affected in diabetes camps as a result of sports, social activities and nutrition. Close glucose monitoring is necessary to reduce glycemic variability, especially hypoglycemia. The aim assessment of glycemic variability and time in range by use of the flash glucose monitoring system (FGMS) in children and adolescents with type 1 diabetes.Materials and Methods:Thirty-three children and adolescents between 10-18 years of age who participated in the 2018 diabetes camp of Ege University were included. Their glycemic variability indexes were recorded.Results:The mean age and duration of diabetes mellitus in the study group was 13.3±0.5 and 4.9±0.7 years respectively. Twelve (43%) of the participants were boys and 16 (57%) were girls. Ten (35.7%) of the participants used continuous subcutaneous insulin infusion (CSII) pump therapy while 18 (64.3%) used multiple dose insulin therapy. When the participants were evaluated according to time in range (TIR), the duration of TIR increased, and level 1 and level 2 hyperglycemia decreased during the camp. Participants using CSII had spent more time in level 2 hypoglycemia before camp, but during and after the camp, similar values were reached for both groups. Before the camp, participants with good metabolic control had a longer duration of hypoglycemia than those participants with poor metabolic control. During and after the camp, level 1 and level 2 hypoglycemia periods were similar between the two groups.Conclusion:In diabetes camp, healthy diet, regular exercise, and close glycemic control improve glycemic variability. By using FGMS, normoglycemia periods can be increased without increasing hypoglycemic attacks. As a result, using FGMS had a positive effect on diabetes management and the control of hypoglycemia periods during the diabetes camp.